Spécificités et généricités des difficultés et besoins d'aide exprimés par les inscrits à un MOOC - Marc Trestini; Richard Cabassut (Centre National d'Enseignement à Distance, 2017)
Among the technopedagogical innovations of the last decade, MOOCs are undoubtedly one of the most significant in the history of digital learning environments. But because of the large number of enrolled students they allow and the resulting variety of the public, these devices have quickly become a real challenge for the technopedagogical engineers responsible for their design or for researchers who want to study their behavior. This is all the more true when one examines the online training courses which are offered to the people enrolled. The variety and multiplicity of the variables involved are difficult to process with traditional analytical techniques. In this paper, we therefore propose to use the exploratory data analysis techniques, using descriptive cluster statistics to determine which difficulties and needs of aid expressed by the members of a MOOC are specific or common to all. We will expose the features that the MOOCs under scrutiny have in common, while emphasizing the specificities of each. The results will have an impact on the help that will be given.